(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the differences and similarities in expressiveness within advertising texts in the Uzbek and German languages. Advertising relies heavily on effective language use, and each language offers unique structures, idioms, and cultural nuances that shape the message’s impact. By comparing these two linguistically and culturally distinct languages, we aim to understand how expressiveness is employed to captivate audiences, influence perceptions, and encourage consumer behavior. The research focuses on the use of linguistic devices such as metaphors, slogans, emotional appeals, and persuasive strategies in advertising.